2017
DOI: 10.1002/rra.3218
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of streamflow and plant species abundance on islets as they relate to ENSO events downstream from an inversion‐type reservoir

Abstract: The goal of this study was to analyse the impacts of the sequence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…During the 2008 growing season (April to September), there were many days when relatively large flows (> 100m³/s) were released [36], such that islets remained submerged during this high flow period. This prolonged immersion led to the near disappearance of terrestrial species on the islets the following year [26]. This clearly shows that the duration of immersion of sites significantly affects the number of terrestrial species.…”
Section: International Journal Of Environmental Sciences and Natural Resources Conclusionmentioning
confidence: 77%
See 1 more Smart Citation
“…During the 2008 growing season (April to September), there were many days when relatively large flows (> 100m³/s) were released [36], such that islets remained submerged during this high flow period. This prolonged immersion led to the near disappearance of terrestrial species on the islets the following year [26]. This clearly shows that the duration of immersion of sites significantly affects the number of terrestrial species.…”
Section: International Journal Of Environmental Sciences and Natural Resources Conclusionmentioning
confidence: 77%
“…Thus, during the growing season (April to September) when water levels are relatively high, the number of terrestrial species decreases on these bars due to the relatively extensive period during which these sites are under water. Dubeau et al [26], for their part, showed that the duration of immersion of islets in springtime downstream from the Matawin dam strongly influences the number of terrestrial species on these islets. Thus, when islets remain under water for long periods in springtime, as was the case in 2008 (La Niña year), the number of terrestrial species decreases markedly to be replaced by obligate wetland species.…”
Section: International Journal Of Environmental Sciences and Natural Resourcesmentioning
confidence: 99%
“…In Quebec, these impacts will be greater downstream of dams characterized by the inversiontype management method than downstream of dams characterized by other types of management methods. This strong variability in the seasonal flows results a gradual increase terrestrial plant species in the low flow channel downstream from Matawin Reservoir dependent on obligate wetland species [30,31]. This aspect should be considered in policy for developing flow management standards intended to restore the ecological integrity of regulated rivers.…”
Section: Discussionmentioning
confidence: 99%